Variance in saccadic eye movements reflects stable traits - Meyhöfer, Inga; Bertsch, Katja; Esser, Moritz; Ettinger, Ulrich (Psychophysiology, 2016)
Saccadic tasks are widely used to study cognitive processes, effects of pharmacological treatments, and mechanisms underlying psychiatric disorders. In genetic studies, it is assumed that saccadic endophenotypes are traits. While internal consistency and temporal stability of saccadic performance is high for most of the measures, the magnitude of underlying trait components has not been estimated, and influences of situational aspects and person by situation interactions have not been investigated. To do so, 68 healthy participants performed prosaccades, antisaccades, and memory-guided saccades on three occasions at weekly intervals at the same time of day. Latent state-trait modeling was applied to estimate the proportions of variance reflecting stable trait components, situational influences, and Person × Situation interaction effects. Mean variables for all saccadic tasks showed high to excellent reliabilities. Intraindividual standard deviations were found to be slightly less reliable. Importantly, an average of 60% of variance of a single measurement was explained by trans-situationally stable person effects, while situation aspects and interactions between person and situation were found to play a negligible role. We conclude that saccadic variables, in standard laboratory settings, represent highly reliable measures that are largely unaffected by situational influences. Extending previous reliability studies, these findings clearly demonstrate the trait-like nature of these measures and support their role as endophenotypes.